PENENTUAN PERLAKUAN TERHADAP KAWASAN PERUMAHAN VILLA JATISARI BEKASI: SUATU PENDEKATAN KONSEP PEMASARAN KAWASAN PERUMAHAN - Dian Setiawan, Heru (Fakultas Teknik Universitas Krisnadwipayana, 2015)
Villa Jatisari Bekasi is a large residential area in Bekasi. Infrastructure, and other social issues may potentially reduced the image of Villa Jatisari Bekasi. Many concepts have been tried to solve the problems declining image of Villa Jatisari Bekasi. One of the concept that can be applied on Villa Jatisari Bekasi is service quality, a concept introduced by Zeithami, Berry, Parasuraman, Lovelock and Fitzsimmons. This paper proposes a quality service’s approach to solve the problem of Villa Jatisari Bekasi by exploring the perception of Villa Jatisari Bekasi’s consumen based on two criterias: performance and importance.